Computer Simulations of Astronomical Objects as seen by the Next Generation Optical Space Telescopes - Mohammed, A. (Iraqi Journal of Science, 2025)
Computer simulations and carried on 200iantity the quality of astronomical objects as seen by the Next Generation Space Telescope (NGST Frese simulations are studied in terms of the modulation ruler function, MIF, of a reference star, and the power spectra of e binery star. The ceste of these simulations are compared with the smelted results the the same astronomical objects as seen via Hubble Space Telescope TIST, and Grand-Based Optical Telescope (GAF in the absence and greases of mesmerteristicbalence, This study là nho extended to examine the percentage frequency recovery of these telescopes from a sundry star of sepoartan is just within the tuit extent of tHubble's psf in the absence and presence of artsspreric urbulencs